2021
DOI: 10.1016/j.psychres.2021.114138
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the UK COVID-19 Psychological Wellbeing Study: Trajectories of anxiety, depression and COVID-19-related stress symptomology

Abstract: COVID-19 has had a negative impact on the mental health of individuals. The aim of the COVID-19 Psychological Wellbeing Study was to identify trajectories of anxiety, depression and COVID-19-related traumatic stress (CV19TS) symptomology during the first UK national lockdown. We also sought to explore risk and protective factors. The study was a longitudinal, three-wave survey of UK adults conducted online. Analysis used growth mixture modelling and logistic regressions. Data was collected from 1958 adults. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 52 publications
(79 reference statements)
8
69
1
Order By: Relevance
“…This finding contrasts with studies in the general population, which show that the high impact at the beginning of the first wave of the pandemic tends to decline after 3–5 weeks of the first wave (Gonzalez-Sanguino et al ., 2020; Daly and Robinson, 2021; Fancourt et al ., 2021; Robinson and Daly, 2021). Nevertheless, some general population studies show a persistently high level of mental health impact through the initial phases of the pandemic (Kikuchi et al ., 2020; McGinty et al ., 2020) while still another study shows that a substantial proportion of the general population maintained high levels of symptoms (McPherson et al ., 2021). A possible explanation of the different trajectory among healthcare workers is the maintained levels of proximal stressors they faced, like other essential workers (Paul et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with studies in the general population, which show that the high impact at the beginning of the first wave of the pandemic tends to decline after 3–5 weeks of the first wave (Gonzalez-Sanguino et al ., 2020; Daly and Robinson, 2021; Fancourt et al ., 2021; Robinson and Daly, 2021). Nevertheless, some general population studies show a persistently high level of mental health impact through the initial phases of the pandemic (Kikuchi et al ., 2020; McGinty et al ., 2020) while still another study shows that a substantial proportion of the general population maintained high levels of symptoms (McPherson et al ., 2021). A possible explanation of the different trajectory among healthcare workers is the maintained levels of proximal stressors they faced, like other essential workers (Paul et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the timing of data collection in relation to the pandemic phase may also have a role. In one study, for example, the authors found that the pre-existing mental health condition was a significant predictor for psychological distress early in the study phase, while the effect disappeared later in the study [ 13 ]. Similarly, they found that people with increasing mental health symptoms have experienced resilience early in the pandemic, which faded later, and in contrast to those who reported high scores in the early weeks, they showed considerable improvement with the pandemic progression [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from studies on the COVID-19 pandemic or similar disasters, suggests that several factors are implicated in the development of mental health and anxiety symptoms; for example, sociodemographic characteristics, such as age, gender, or receiving inadequate social support have significantly impacted mental health outcomes during such difficult times [ 5 , 12 , 13 , 14 ]. Additionally, having an infected family member with COVID-19 or excessive fear of becoming infected were also associated with stress-related symptoms [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring social distancing and reducing interpersonal relationships are needed worldwide to combat the present COVID-19 pandemic. It has various effects such as increased stress, heightened anxiety, and worsening depression [ 1 , 2 ]. Moreover, it has chronic effects on children’s social life and mental health.…”
Section: Introductionmentioning
confidence: 99%